Cryptanalysis of certificateless authenticated key agreement protocols. (9th July 2020) - Zeng, Runzhi; Wang, Libin
In this work, we cryptanalyse two certificateless authenticated key agreement (CL-AKA) protocols, Bala et al. (2018) and Xie et al. (2019), which are recently proposed claiming provable security. Specifically, we show impersonation attacks against the two protocols with successful probability 1 in extended eCK model using at most two queries. Then, the process of our cryptanalysis is abstracted to a general method for cryptanalysing a specific class of CL-AKA protocols which we call linearly-expressible CL-AKA protocol . Our method suggests new security requirements of CL-AKA protocols.